Avaliação da saúde de populações ribeirinhas atingidas pelo desastre de Brumadinho. - Camila Francisco Moreira (2021)
On January 25, 2019, dam I at the Córrego do Feijão mine in Brumadinho, Minas Gerais. The impacts of the disaster on the population need to be known and measured. In this way, the objective of this study was to evaluate the environmental exposure to metals and metalloids, as well as the health of the population residing in the communities near the Paraopeba River. 121 volunteers from the municipalities of Mário Campos, Juatuba e São Joaquim de Bicas participated in this cross-sectional study. Data were obtained through self-repot in a pre-collection interview, blood and urine samples Blood were collected for analysis of: blood count, renal and hepatic function biomarkers by biochemical measurements and metals and metalloids by DMA (Direct Mercury Analysis) and ICP-MS (Inductively Coupled Plasma Mass Spectrometry). Volunteers reported hypertension (47), dermatites, allergies and skin irritation (26), diabetes (17) and mental health conditions (11). The blood count demonstrated probable incidences of erythrocytosis (23,3%), erythropenia (8,6%), hemoglobin deficiency (6.9%), reduction in RDW-CV (68.1%), leukocytosis (12.1%) and eosinophilia (9.5%). The measurement of liver and kidney function biomarkers showed an increase in: alkaline phosphatase (23.5%), AST/TGO (47.3%) and serum urea (75%). In addition, 13 volunteers had an AST/ ALT ratio greater than 2 and 4 albumin results were above 30 mg g -1 creatinine. The validated methodology for mercury analysis was satisfactory, there were 15 levels above the detection limit of the method, 2 of them above the quantification limit, in whole blood. The multivariate analysis indicates similarity between the populations evaluated in terms of global health parameters accessed. The methodology for multielement analysis of metals and metalloids was optimized for further methodological validation and dosage of potentially toxic elements. The present work highlights the importance of health assessments and environmental exposure to metals and metalloids of populations bordering the Paraopeba River, as well as the need to expand such investigations in order to provide better health care and guide decision-making in public policies.